Istilah Rosario: Suatu Metafora - Pasi, Gregorius (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2023)
Abstract The rosary is a simple but rich form of marian devotion. This article is intended to present one of these riches, namely the term of rosary itself. Therefore, the title of this article is: “The Term of Rosary: A Metaphor”. The focus of this article is to answer the following two questions. First, what is the impact of using the term of rosary on the marian devotees? Second, how can the term of rosary have an impact on the marian devotees? In order to answer these questions, we use the critical analysis and critical dialectic on the elements related to the theme of this research. Through this critical analysis and dialectical analysis we found the following two things: first, metaphor can transforms the marian devotee’s understanding, feelings dan attitudes towards the marian devotion intended by the metaphor the rosary; secondly, for the metaphor to have an impact on marian devotees, they must first realize that the term is a metaphor not only in the broad sense, but also in the strict sense, besides that, the marian devotees must have an experince related to a rose garden (rosarium) or roses (rosa). Abstrak Rosario merupakan suatu bentuk devosi marial yang sederhana namun kaya. Tulisan ini dimaksudkan untuk menampilkan salah satu kekayaan itu, yaitu istilah “rosario” itu sendiri. Karena itu, judul tulisan adalah: “Istilah Rosario: Suatu Metafora”. Fokus tulisan ini adalah menjawab kedua pertanyaan berikut. Pertama, apa dampak penggunaan istilah “rosario” bagi para devosan marial? Kedua, bagaimana supaya istilah rosario itu berdampak pada para devosan marial? Dalam rangka menjawab pertanyaan itu, kami menggunakan metode analisis kritis dan dialektika kritis atas unsur-unsur terkait tema penelitian ini. Melalui analisis kritis dan dialektika itu, kami menemukan kedua hal berikut: pertama, metafora dapat mentransformasi pemahaman, perasaan dan sikap devosan marial terhadap bentuk devosi marial yang dimaksudkan dengan metafora itu; kedua, agar metafora itu berdampak pada para dovosan marial, pertama-tama mereka harus menyadari bahwa istilah itu merupakan suatu metafora, bukan hanya dalam arti luas, tetapi juga dalam arti sempit; selain itu, para devosan marial harus memiliki pengalaman terkait dengan taman mawar (rosarium) atau mawar (rosa). Kata Kunci: Rosario, metafora, devosi marial, Mazmur, transformasi.